JEJAK DIGITAL DALAM JURNALISME: MEDIA SOSIAL DAN MEDIA DARING DI INDONESIA - Utami Rosemarwati; Lisa Lindawati (LodDos Institute, 2023)
This research investigates the role of digital footprints in journalism practice, focusing on the influence of social media and online media in Indonesia. The development of information and communication technology has significantly changed the landscape of media and journalism, allowing wider access to information, but also raising a number of challenges related to the truth, integrity, and social impact of news and information spread on digital platforms. In this research, we use qualitative approaches and case studies to analyse how social media and online media have influenced the way news is produced, consumed and shared in Indonesia. We also explore issues related to data security, privacy, and the growing spread of fake news in the digital media ecosystem. Through interviews with media practitioners and content analysis, this research tries to unpack the complex dynamics that affect journalism in the digital age. The results of this study provide valuable insights into how journalism adapts to technological changes and societal demands in presenting accurate and relevant information. This research also provides a basis for a better understanding of the challenges and opportunities faced by media and journalists in maintaining the integrity and ethics of journalism in the digital era in Indonesia.